Academic Leadership in the New Normal - Jeff Buller (Academic Chairpersons Conference Proceedings, 2022)
The COVID-19 pandemic. The assault on the U.S. capitol. Global warming. Toxic polarization. These and other factors have created what many in higher education now refer to as “the New Normal.” It's a period when many of our former assumptions about higher education—including the reason for going to college itself—are increasingly being called into question. How can department chairs lead most effectively in this altered landscape of higher education? What has really changed, and what has remained relatively untouched by recent events? In this workshop, participants will explore how to plan and guide their programs when the only thing they can expect is more of the unexpected.
Keywords: leadership; new normal; challenges; uncertainty; planning